Tpack Level and Tpack Self-Efficacy of Pre-Service Teachers: Implications For An Sdg-Aligned Professional Development Plan - Mark Lawrence Y. Dupitas (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
In response to the growing demand for technology-integrated and sustainable education, this study examined the Technological Pedagogical Content Knowledge (TPACK) level and TPACK self-efficacy of pre-service teachers majoring in Bachelor of Technology and Livelihood Education (BTLEd) in the Province of Tarlac, Philippines. The study was grounded in the TPACK Framework by Mishra and Koehler and Bandura’s Self-Efficacy Theory, which explains the integration of technology, pedagogy, and content knowledge, as well as the role of teachers’ confidence in effective teaching. A descriptive design with survey questionnaires was used. Data were analyzed using Pearson correlation. Results revealed a strong positive correlation between overall TPACK and TPACK self-efficacy (r = .828, p < .001, N = 89), indicating that higher TPACK levels are significantly associated with stronger teaching confidence. These findings indicate that higher levels of TPACK are associated with greater confidence in teaching, lesson design, addressing diverse learners, and technology-based assessment. However, specific areas of weakness were identified in both TPACK and self-efficacy, particularly in advanced technology integration and sustained classroom application. Identified gaps guided the development of an SDG-aligned professional development plan to strengthen teacher competence and advance SDG 4. The findings highlight the need for targeted training to enhance pre-service teachers’ TPACK and self-efficacy.